Adhesive composition and adhesive tape

By using acrylic copolymers and terpene phenol resins with specific structures in the adhesive composition, the problem that the adhesive composition in the prior art is difficult to take into account both high adhesion and optical transparency when fixing optical members in the adhesive composition is solved. , excellent adhesion and transparency in the case of thin thickness are achieved.

CN119487144APending Publication Date: 2025-02-18SEKISUI CHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380054319.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-31
Filing Date
2023-10-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The conventional adhesive compositions are difficult to take into account both high adhesion and optical transparency when fixing optical members, especially when the coating thickness is thin, the adhesion is insufficient.

Method used

A binder composition containing an acrylic copolymer having structural units from an alkyl (meth)acrylate and an olefin-based polymer having a polymerizable unsaturated double bond at the end, and in the binder Terpenephenol resin or derivatives thereof are added in an appropriate amount to the composition to improve adhesion.

Benefits of technology

Even in the case of thin thickness, excellent adhesion and optical transparency can be achieved, and are suitable for fixing small and thin electronic devices and optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to an adhesive composition which contains an acrylic copolymer having a structural unit derived from an alkyl (meth) acrylate and a structural unit derived from an olefin polymer having a polymerizable unsaturated double bond at a terminal, and which satisfies the following first configuration and / or the following second configuration. The first composition contains at least one tackifying resin (T1) selected from the group consisting of terpene-phenol resins, hydrogenated terpene-phenol resins, and xylene resins, with the content of T1 being 5-50 parts by mass, and does not contain a tackifying resin (T2) different from T1, or in the case where T2 is contained, the content is 10 parts by mass or less per 100 parts by mass of the acrylic copolymer. The second configuration is that the acrylic copolymer has a structural unit derived from a polar functional group-containing monomer and has a structural unit derived from an alkyl (meth) acrylate having 1-4 carbon atoms and an alkyl group bonded to an oxygen atom of an ester bond, and the content of the structural unit is 30-90 mass%. The adhesive composition does not contain a tackifying resin, or the content of the tackifying resin is 5 parts by mass or less per 100 parts by mass of the acrylic copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition and also to an adhesive tape having an adhesive layer containing the adhesive composition. Background Art

[0002] Adhesive tapes are used for assembly of portable electronic devices such as mobile phones and personal digital assistants (PDAs) (for example, Patent Documents 1 and 2). Adhesive tapes are also used for bonding optical components (for example, Patent Document 3).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-242541

[0006] Patent Document 2: Japanese Patent Application Publication No. 2009-258274

[0007] Patent Document 3: Japanese Patent Application Publication No. 2012-214544 Summary of the invention

[0008] Problems to be solved by the invention

[0009] Adhesive compositions and adhesive tapes used for fixing optical components are required to have both adhesive strength and optical transparency. In particular, in recent years, as electronic devices and devices have become smaller and thinner, it has been required to reduce the thickness of the applied adhesive composition and the thickness of the adhesive tape. However, if the thickness of the applied adhesive composition and the thickness of the adhesive tape are reduced, sufficient adhesive strength cannot be exerted.

[0010] Furthermore, conventionally, adhesive compositions and adhesive tapes have been provided with tackifier resins to enhance adhesive strength. However, when adhesive compositions and adhesive tapes contain tackifier resins, turbidity or yellowing may occur, and optical transparency may not be obtained.

[0011] An object of the present invention is to provide a pressure-sensitive adhesive composition that can achieve both excellent adhesive strength and excellent optical transparency even when applied at a thin thickness. Another object of the present invention is to provide a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive composition.

[0012] Means for solving problems

[0013] The present disclosure 1 relates to an adhesive composition comprising an acrylic copolymer having a structural unit derived from an alkyl (meth)acrylate and a structural unit derived from an olefin polymer having a polymerizable unsaturated double bond at a terminal, wherein the adhesive composition satisfies at least one structure selected from the following first structure and the following second structure.

[0014] A first configuration: containing at least one tackifier resin T1 selected from terpene phenol resins, hydrogenated terpene phenol resins and xylene resins, wherein the content of the tackifier resin T1 is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the acrylic copolymer, and the adhesive composition does not contain a tackifier resin T2 different from the terpene phenol resins, hydrogenated terpene phenol resins and xylene resins, or contains the tackifier resin T2, and when the adhesive composition contains the tackifier resin T2, the content of the tackifier resin T2 is 10 parts by mass or less relative to 100 parts by mass of the acrylic copolymer;

[0015] The second configuration: the acrylic copolymer has a structural unit derived from a monomer containing a polar functional group, the acrylic copolymer has a structural unit derived from an alkyl (meth)acrylate in which the number of carbon atoms of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 4 or less, in the acrylic copolymer, the content of the structural unit derived from the alkyl (meth)acrylate in which the number of carbon atoms of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 4 or less is 30% by mass or more and 90% by mass or less, the adhesive composition does not contain a tackifier resin or contains a tackifier resin, and when containing a tackifier resin, the content of the tackifier resin is 5 parts by mass or less relative to 100 parts by mass of the acrylic copolymer.

[0016] Present Disclosure 2 relates to the pressure-sensitive adhesive composition of Present Disclosure 1, wherein in the first configuration, the acrylic copolymer has a structural unit derived from a polar functional group-containing monomer.

[0017] The present disclosure 3 relates to the adhesive composition of the present disclosure 1 or 2, wherein the structural unit derived from the monomer containing a polar functional group comprises at least one structural unit selected from the group consisting of structural units derived from a monomer containing a carboxyl group and structural units derived from a monomer containing a hydroxyl group.

[0018] The present disclosure 4 relates to the adhesive composition of the present disclosure 3, wherein the structural unit derived from the monomer containing a polar functional group includes the structural unit derived from the monomer containing a carboxyl group.

[0019] The present disclosure 5 relates to the pressure-sensitive adhesive composition of the present disclosure 4, wherein in the second configuration, the content of the structural unit derived from the carboxyl group-containing monomer in the acrylic copolymer is 10% by mass or less.

[0020] The present disclosure 6 relates to the pressure-sensitive adhesive composition of the present disclosure 4 or 5, wherein the content of the structural unit derived from the carboxyl group-containing monomer in the acrylic copolymer is 1% by mass or less.

[0021] Disclosure 7 relates to the adhesive composition of Disclosure 3, 4, 5 or 6, wherein the structural unit derived from the monomer containing a polar functional group includes the structural unit derived from the monomer containing a hydroxyl group.

[0022] Present disclosure 8 relates to the adhesive composition of present disclosure 1, 2, 3, 4, 5, 6 or 7, wherein in the first configuration, the tackifier resin T1 includes the hydrogenated terpene phenol resin.

[0023] Disclosure 9 relates to the adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7 or 8, wherein in the second configuration, the acrylic copolymer has a structural unit derived from an alkyl (meth)acrylate having an alkyl group bonded to an oxygen atom of an ester bond and having 1 to 2 carbon atoms,

[0024] In the acrylic copolymer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester having 1 to 2 carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 10% to 60% by mass.

[0025] Disclosure 10 relates to the adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein in the second configuration, the acrylic copolymer has a structural unit derived from an alkyl (meth)acrylate having an alkyl group bonded to an oxygen atom of an ester bond and having 3 or more and 4 or less carbon atoms,

[0026] In the acrylic copolymer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 60% by mass or more.

[0027] Present Disclosure 11 relates to an adhesive tape having an adhesive layer containing the adhesive composition of Present Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0028] Present disclosure 12 is directed to the pressure-sensitive adhesive tape of present disclosure 11, wherein the pressure-sensitive adhesive layer has a gel fraction of 10% by mass or more and 80% by mass or less.

[0029] Present disclosure 13 relates to the pressure-sensitive adhesive tape of present disclosure 11 or 12, wherein the pressure-sensitive adhesive layer has a thickness of 15 μm or less.

[0030] Disclosure 14 relates to the adhesive tape of Disclosure 13, which has a 180° peeling force on glass at 23° C. of 9 N / inch or more after being left to stand at 23° C. for 24 hours after being attached.

[0031] Present disclosure 15 relates to the pressure-sensitive adhesive tape of present disclosure 11, 12, 13 or 14, wherein the haze at 23° C. is 1.0% or less.

[0032] Disclosure 16 relates to the adhesive tape of Disclosure 11, 12, 13, 14 or 15, which does not have a substrate.

[0033] Hereinafter, the present invention will be described in detail.

[0034] It should be noted that matters common to the first configuration and the second configuration are described in a form not particularly specified.

[0035] The present inventors studied the composition of the adhesive composition so that it contained an acrylic copolymer having a specific structure, and studied the content and type of the tackifying resin contained in the adhesive composition. As a result, it was found that even when the coating thickness was thin, an adhesive composition that could achieve both excellent adhesion and excellent optical transparency could be obtained, thereby completing the present invention.

[0036] The pressure-sensitive adhesive composition of the present invention contains an acrylic copolymer having a structural unit derived from an alkyl (meth)acrylate and a structural unit derived from an olefin-based polymer having a polymerizable unsaturated double bond at a terminal.

[0037] In addition, in this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid.

[0038] The acrylic copolymer has the following structure: the structural unit from the olefin polymer with polymerizable unsaturated double bonds at the end is condensed by interaction, forming an approximate crosslinking point (Japanese: simulating a bridge point). By making the acrylic copolymer adopt such a structure, the adhesive composition shows a hard property like a crosslinked adhesive composition when the strain is small, and the holding power is improved. On the other hand, when the peeling stress is applied and the strain becomes large, the approximate crosslinking is disconnected, and the molecules of the acrylic copolymer are elongated, so the adhesive composition shows a high property of flexibility, and the bonding power is improved. That is, by making the adhesive composition contain the acrylic copolymer, the bonding power and the holding power of the adhesive composition are improved.

[0039] Examples of the alkyl (meth)acrylate include those obtained by dehydration condensation of (meth)acrylic acid and an alcohol having a linear or branched alkyl group having 1 to 24 carbon atoms. Specifically, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, n-heptyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, and the like are mentioned. In addition, these alkyl (meth)acrylates may be used alone or in combination of two or more.

[0040] In the acrylic copolymer, the preferred lower limit of the content of the structural unit derived from the (meth) alkyl acrylate is 50% by mass, and the preferred upper limit is 95% by mass. By making the content of the structural unit derived from the (meth) alkyl acrylate within the above range, the adhesive force and holding power of the adhesive composition are further improved. The more preferred lower limit of the content of the structural unit derived from the (meth) alkyl acrylate is 60% by mass, the further preferred lower limit is 70% by mass, the more preferred upper limit is 90% by mass, and the further preferred upper limit is 85% by mass.

[0041] The olefin polymer having a polymerizable unsaturated double bond at one terminal may have a polymerizable unsaturated double bond at one terminal or at both terminals. Among them, an olefin polymer having a polymerizable unsaturated double bond at one terminal is preferred from the viewpoint of easily forming an appropriate number of proximal crosslinks.

[0042] Examples of the olefin polymer having a polymerizable unsaturated double bond at a terminal include ethylene-butene copolymers, ethylene-propylene copolymers, ethylene polymers, propylene polymers, butene polymers, etc., each having a group having a polymerizable unsaturated double bond at one or both terminals.

[0043] In addition, these olefin polymers having a polymerizable unsaturated double bond at the terminal may be used alone or in combination of two or more.

[0044] Examples of the group having a polymerizable unsaturated double bond include a (meth)acryloyl group, a vinyl ether group, a styryl group, etc. Among them, a (meth)acryloyl group is preferred because of its excellent copolymerizability with the (meth)acrylic acid alkyl ester.

[0045] Examples of the olefin polymer having a (meth)acryloyl group at a terminal include an ethylene macromonomer having a (meth)acryloyl group at one terminal, a propylene macromonomer having a (meth)acryloyl group at one terminal, an ethylene-butylene macromonomer having a (meth)acryloyl group at one terminal, and an ethylene-propylene macromonomer having a (meth)acryloyl group at one terminal. Among them, from the viewpoint of facilitating adjustment of the glass transition temperature described later within an appropriate range and further improving the adhesive force of the adhesive composition, an ethylene-butylene macromonomer having a (meth)acryloyl group at one terminal and an ethylene-propylene macromonomer having a (meth)acryloyl group at one terminal are preferred.

[0046] In addition, in this specification, a "macromonomer" refers to a monomer having a polymerizable functional group and having a weight average molecular weight of about 1,000 to 100,000.

[0047] In the above-mentioned acrylic copolymer, the preferred lower limit of the content of the structural unit of the olefin polymer having a polymerizable unsaturated double bond at the end is 5% by mass, and the preferred upper limit is 30% by mass. By making the content of the structural unit of the olefin polymer having a polymerizable unsaturated double bond at the end to be 5% by mass or more, the above-mentioned acrylic copolymer forms a moderate amount of approximate crosslinking, and the adhesion and holding power of the above-mentioned adhesive composition are further improved. By making the content of the structural unit of the olefin polymer having a polymerizable unsaturated double bond at the end to be 30% by mass or less, the cohesive failure of the above-mentioned adhesive composition can be further suppressed. The more preferred lower limit of the content of the structural unit of the olefin polymer having a polymerizable unsaturated double bond at the end is 8% by mass, the further preferred lower limit is 10% by mass, the more preferred upper limit is 27% by mass, and the further preferred upper limit is 25% by mass.

[0048] The adhesive composition of the present invention satisfies at least one structure selected from the following first structure and the following second structure.

[0049] A first configuration: containing at least one tackifier resin T1 selected from terpene phenol resins, hydrogenated terpene phenol resins and xylene resins, wherein the content of the tackifier resin T1 is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the acrylic copolymer, and the adhesive composition does not contain a tackifier resin T2 different from the terpene phenol resins, hydrogenated terpene phenol resins and xylene resins, or contains the tackifier resin T2, and when the adhesive composition contains the tackifier resin T2, the content of the tackifier resin T2 is 10 parts by mass or less relative to 100 parts by mass of the acrylic copolymer;

[0050] The second configuration: the acrylic copolymer has a structural unit derived from a monomer containing a polar functional group, the acrylic copolymer has a structural unit in which the carbon number of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 4 or less, in which the content of the structural unit derived from the (meth)acrylic acid alkyl ester in which the carbon number of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 4 or less is 30% by mass or more and 90% by mass or less, and the adhesive composition does not contain a tackifier resin or contains a tackifier resin, and when containing a tackifier resin, the content of the tackifier resin is 5 parts by mass or less relative to 100 parts by mass of the acrylic copolymer.

[0051] The adhesive composition of the present invention satisfies at least one configuration selected from the following first configuration and the following second configuration, thereby achieving both excellent adhesive strength and excellent optical transparency even when the thickness is thin.

[0052] In the first configuration, the acrylic copolymer preferably has a structural unit derived from an alkyl (meth)acrylate in which the number of carbon atoms of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 8 or less. In the case of having a structural unit derived from an alkyl (meth)acrylate in which the number of carbon atoms of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 4 or less, the polarity of the acrylic copolymer becomes larger, and the interaction with the adherend is further improved, thereby further improving the adhesive force of the adhesive composition. In addition, in the case of having a structural unit derived from an alkyl (meth)acrylate in which the number of carbon atoms of the alkyl group bonded to the oxygen atom of the ester bond is 4 or more and 8 or less, it is easy to adjust the glass transition temperature described later to an appropriate range, and the adhesive force of the adhesive composition is further improved.

[0053] The structural unit derived from an alkyl (meth)acrylate having 1 to 8 carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond may be used alone or in combination of two or more.

[0054] In the second configuration, the acrylic copolymer has a structural unit derived from an alkyl (meth)acrylate in which the alkyl group bonded to the oxygen atom of the ester bond has 1 to 4 carbon atoms. Since the acrylic copolymer has the structural unit derived from an alkyl (meth)acrylate in which the alkyl group bonded to the oxygen atom of the ester bond has 1 to 4 carbon atoms, the polarity of the acrylic copolymer increases, the interaction with the adherend increases, and the adhesive force of the pressure-sensitive adhesive composition increases.

[0055] In the second configuration, in the acrylic copolymer, the lower limit of the content of the structural unit of the (meth) acrylic acid alkyl ester having 1 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 30% by mass and the upper limit is 90% by mass. By making the content of the structural unit of the (meth) acrylic acid alkyl ester having 1 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond greater than 30% by mass, the polarity of the acrylic copolymer becomes larger, the interaction with the adherend is improved, and the adhesive force of the adhesive composition is improved. By making the content of the structural unit of the (meth) acrylic acid alkyl ester having 1 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond less than 90% by mass, the structural unit of the olefin polymer having a polymerizable unsaturated double bond at the end in the acrylic copolymer can form a high cohesive approximate crosslinking point. As a result, the adhesive force and holding force of the adhesive composition are improved. The content of the structural unit derived from the alkyl (meth)acrylate in which the alkyl group bonded to the oxygen atom of the ester bond has 1 to 4 carbon atoms is preferably 40% by mass in the lower limit, more preferably 50% by mass, and preferably 85% by mass in the upper limit, more preferably 80% by mass.

[0056] Examples of the alkyl (meth)acrylate in which the alkyl group bonded to the oxygen atom of the ester bond has 1 to 4 carbon atoms include those obtained by dehydration condensation of (meth)acrylic acid and an alcohol having a linear or branched alkyl group having 1 to 4 carbon atoms. Specifically, examples include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, and isobutyl (meth)acrylate.

[0057] In the second configuration, from the viewpoint of the adhesive strength of the adhesive composition, the acrylic copolymer preferably has a structural unit derived from an alkyl (meth)acrylate having 1 or more and 2 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond. In the acrylic copolymer, the preferred lower limit of the content of the structural unit derived from an alkyl (meth)acrylate having 1 or more and 2 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 10% by mass, and the preferred upper limit is 60% by mass. By setting the content of the structural unit derived from an alkyl (meth)acrylate having 1 or more and 2 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond to 10% by mass or more, the polarity of the acrylic copolymer becomes larger, the interaction with the adherend is further improved, and the adhesive strength of the adhesive composition is further improved. By making the content of the structural unit derived from the (meth)acrylic acid alkyl ester in which the carbon number of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 2 or less to 60 mass % or less, it is easy to adjust the glass transition temperature of the acrylic copolymer described later to an appropriate range, and the adhesive force of the adhesive composition is further improved. The more preferred lower limit of the content of the structural unit derived from the (meth)acrylic acid alkyl ester in which the carbon number of the alkyl group bonded to the oxygen atom of the ester bond is 1 or more and 2 or less is 15 mass %, and the further preferred lower limit is 30 mass %.

[0058] In the second configuration, from the viewpoint of the optical transparency of the adhesive composition, the acrylic copolymer preferably has a structural unit derived from an alkyl (meth)acrylate having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond. In the acrylic copolymer, the preferred lower limit of the content of the structural unit derived from the alkyl (meth)acrylate having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 60% by mass. By making the content of the structural unit derived from the alkyl (meth)acrylate having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond 60% by mass or more, the approximate crosslinking point formed by the aggregation of the structural unit derived from the olefin polymer having a polymerizable unsaturated double bond at the terminal becomes smaller, and the optical transparency of the adhesive composition is further improved. The more preferred lower limit of the content of the structural unit derived from the alkyl (meth)acrylate having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 70% by mass, and the further preferred lower limit is 75% by mass.

[0059] In addition, the preferred upper limit of the content of the structural unit derived from the (meth) alkyl acrylate having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 90% by mass. By making the content of the structural unit derived from the (meth) alkyl acrylate having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond to be 90% by mass or less, the adhesive force is further improved. The more preferred upper limit of the content of the structural unit derived from the (meth) alkyl acrylate having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 85% by mass, and the further preferred upper limit is 80% by mass.

[0060] In the second configuration, the structural unit derived from the (meth)acrylic acid alkyl ester having 1 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond may be used alone or in combination of two or more. Among them, it is preferred to use the structural unit derived from the (meth)acrylic acid alkyl ester having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond and the structural unit derived from the (meth)acrylic acid alkyl ester having 1 or more and 2 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond in combination. By using the structural unit derived from the (meth)acrylic acid alkyl ester having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond, it is easy to adjust the glass transition temperature of the acrylic copolymer described below to the range described below, and the adhesive force of the adhesive composition is further improved. In addition, by using the structural unit derived from the (meth)acrylic acid alkyl ester having 1 or more and 2 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond, the polarity of the acrylic copolymer becomes larger, the interaction with the adherend is further improved, and the adhesive force of the adhesive composition is further improved. That is, by using in combination the structural unit derived from the alkyl (meth)acrylate in which the alkyl group bonded to the oxygen atom of the ester bond has 3 to 4 carbon atoms and the structural unit derived from the alkyl (meth)acrylate in which the alkyl group bonded to the oxygen atom of the ester bond has 1 to 2 carbon atoms, the adhesive force of the adhesive composition is further improved.

[0061] In the second configuration, the acrylic copolymer has a structural unit derived from a monomer containing a polar functional group. By making the acrylic copolymer have the structural unit derived from a monomer containing a polar functional group, the interaction with the adherend is improved, so the adhesive force and the holding power of the adhesive composition are improved. In addition, when the adhesive composition contains a crosslinking agent described later, the acrylic copolymer is crosslinked with the crosslinking agent, so that the adhesive force and the holding power of the adhesive composition are improved. By adjusting the crosslinking degree at this time, the gel fraction of the adhesive layer described later can be adjusted to an appropriate range.

[0062] In addition, in the first configuration, it is preferred that the acrylic copolymer has a structural unit derived from a monomer containing a polar functional group. By making the acrylic copolymer have the structural unit derived from a monomer containing a polar functional group, the interaction with the adherend is further improved, so the adhesive force and holding power of the adhesive composition are further improved. In addition, when the adhesive composition contains a crosslinking agent described later, the acrylic copolymer is crosslinked with the crosslinking agent, so that the adhesive force and holding power of the adhesive composition are further improved. By adjusting the crosslinking degree at this time, the gel fraction of the adhesive layer described later can be adjusted to an appropriate range.

[0063] Examples of the above-mentioned polar functional group-containing monomer include: carboxyl-containing monomers, hydroxyl-containing monomers, amide-containing monomers, amino-containing monomers, etc. Among them, from the viewpoint of further improving the adhesion and holding power of the above-mentioned adhesive composition, the above-mentioned polar functional group-containing monomer preferably includes at least one selected from carboxyl-containing monomers and hydroxyl-containing monomers. That is, the structural unit derived from the above-mentioned polar functional group-containing monomer preferably includes at least one structural unit selected from the structural unit derived from the carboxyl-containing monomer and the structural unit derived from the hydroxyl-containing monomer.

[0064] In addition, these polar functional group-containing monomers may be used alone or in combination of two or more.

[0065] Since the acrylic copolymer has the structural unit derived from the carboxyl group-containing monomer, the interaction with the adherend is further enhanced, and thus the adhesive force and holding power of the pressure-sensitive adhesive composition are further enhanced.

[0066] Examples of the carboxyl group-containing monomer include unsaturated carboxylic acids such as (meth)acrylic acid, (meth)acryloyl acetic acid, (meth)acryloyl propionic acid, (meth)acryloyl butyric acid, (meth)acryloyl valeric acid, crotonic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, and itaconic acid.

[0067] In the first configuration, in the acrylic copolymer, the preferred upper limit of the content of the structural unit derived from the carboxyl group-containing monomer is 1% by mass. By making the content of the structural unit derived from the carboxyl group-containing monomer less than 1% by mass, the metal corrosiveness of the adhesive composition is further reduced. The more preferred upper limit of the content of the structural unit derived from the carboxyl group-containing monomer is 0.5% by mass.

[0068] In addition, from the viewpoint of metal corrosivity, the acrylic copolymer preferably does not have a structural unit derived from the carboxyl group-containing monomer.

[0069] In the second configuration, in the acrylic copolymer, the preferred upper limit of the content of the structural unit derived from the carboxyl-containing monomer is 10% by mass. By making the content of the structural unit derived from the carboxyl-containing monomer 10% by mass or less, the metal corrosiveness of the adhesive composition is further reduced. The more preferred upper limit of the content of the structural unit derived from the carboxyl-containing monomer is 1% by mass.

[0070] In addition, from the viewpoint of metal corrosivity, the acrylic copolymer preferably does not have a structural unit derived from the carboxyl group-containing monomer.

[0071] When the acrylic copolymer has the structural unit derived from the hydroxyl group-containing monomer, crosslinking between the acrylic copolymer and adherend molecules by a crosslinking agent becomes easier to occur, and the adhesive force and holding power of the pressure-sensitive adhesive composition are further improved.

[0072] Examples of the hydroxyl group-containing monomer include 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate.

[0073] In the above-mentioned acrylic copolymer, the preferred lower limit of the content of the structural unit from the hydroxyl-containing monomer is 0.01% by mass, and the preferred upper limit is 2% by mass. By making the content of the structural unit from the hydroxyl-containing monomer more than 0.01% by mass, the crosslinking of the above-mentioned acrylic copolymer with the help of a crosslinking agent becomes easier to occur, and the adhesion and holding power of the above-mentioned adhesive composition are further improved. By making the content of the structural unit from the hydroxyl-containing monomer less than 2% by mass, the above-mentioned acrylic copolymer will not become too hard, and the adhesion of the above-mentioned adhesive composition is further improved. The more preferred lower limit of the content of the structural unit from the hydroxyl-containing monomer is 0.05% by mass, and the more preferred upper limit is 1% by mass.

[0074] Examples of the amide group-containing monomer include N-vinyl-2-pyrrolidone, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N-isopropyl(meth)acrylamide.

[0075] Examples of the amino group-containing monomer include (meth)acryloylmorpholine, 2-dimethylaminoethyl (meth)acrylate, and 2-diethylaminoethyl (meth)acrylate.

[0076] In the acrylic copolymer, the preferred lower limit of the total content of the structural units from the monomers containing polar functional groups is 0.1% by mass, and the preferred upper limit is 10% by mass. By making the total content of the structural units from the monomers containing polar functional groups more than 0.1% by mass, the interaction between the acrylic copolymer and the adherend is further improved, so the adhesion and retention of the adhesive composition are further improved. In addition, in the case where the adhesive composition contains a cross-linking agent described later, the cross-linking of the acrylic copolymer by means of the cross-linking agent becomes easier to occur, and the adhesion and retention of the adhesive composition are further improved. By making the total content of the structural units from the monomers containing polar functional groups less than 10% by mass, the acrylic copolymer will not become too hard, and the adhesion of the adhesive composition is further improved. The more preferred lower limit of the total content of the structural units from the monomers containing polar functional groups is 1% by mass, the further preferred lower limit is 3% by mass, the more preferred upper limit is 8% by mass, and the further preferred upper limit is 6% by mass.

[0077] The glass transition temperature (Tg) of the acrylic copolymer is preferably in the range of -100°C to 200°C, and the more preferred upper limit is -20°C. By setting the glass transition temperature of the acrylic copolymer to -20°C or lower, the molecules of the acrylic copolymer are more easily elongated, and thus the adhesive force of the adhesive composition is further improved. The more preferred upper limit of the glass transition temperature of the acrylic copolymer is -30°C, and the particularly preferred upper limit is -35°C. In addition, when the adhesive composition contains a plurality of acrylic copolymers, it is preferred that the glass transition temperature of all the acrylic copolymers contained in the adhesive composition is -20°C or lower.

[0078] It should be noted that the glass transition temperature of the acrylic copolymer can be measured by differential scanning calorimetry. More specifically, the glass transition temperature of the acrylic copolymer can be measured by the following method, etc.: in a nitrogen atmosphere (nitrogen flow, flow rate 50 mL / min), using a differential scanning calorimeter (Seiko Instruments, "220C" or the like), according to JIS K6240: 2011, under the conditions of a measurement temperature of -100°C to 200°C and a heating rate of 10°C / min.

[0079] The glass transition temperature of the acrylic copolymer can be adjusted by the type and amount of the monomers that are the materials of the acrylic copolymer.

[0080] The preferred lower limit of the weight average molecular weight (Mw) of the acrylic copolymer is 500,000, and the preferred upper limit is 2,000,000. By making the weight average molecular weight of the acrylic copolymer greater than 500,000, the cohesive force of the body (Japanese: バルク) of the adhesive composition becomes larger, and the adhesive force and heat resistance of the adhesive composition are further improved. By making the weight average molecular weight of the acrylic copolymer less than 2,000,000, the adhesive composition will not become too hard, and the adhesive force is further improved. The more preferred lower limit of the weight average molecular weight of the acrylic copolymer is 650,000, and the more preferred upper limit is 1,500,000.

[0081] The preferred lower limit of the polydispersity coefficient of the acrylic copolymer is 1.0, and the preferred upper limit is 6.0. By making the polydispersity coefficient of the acrylic copolymer within the above range, the adhesive force and holding power of the adhesive composition are further improved. The more preferred lower limit of the polydispersity coefficient of the acrylic copolymer is 1.5, and the more preferred upper limit is 4.5.

[0082] It should be noted that the polydispersity coefficient refers to the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn).

[0083] In this specification, the weight average molecular weight, the number average molecular weight and the polydispersity coefficient can be obtained based on the molecular weight distribution in terms of polystyrene measured using gel permeation chromatography (GPC). Specifically, for example, they can be obtained by measuring using gel permeation chromatography (manufactured by Waters, "2690 Separations Module" etc.) under the following conditions.

[0084] Solvent: Tetrahydrofuran

[0085] Sample flow rate: 1mL / min

[0086] Detector: Differential Refractometer RI

[0087] Column: GPC KF-806L (manufactured by Showa Denko K.K.)

[0088] Column temperature (measurement temperature): 40°C

[0089] Injection volume: 20 μL

[0090] In the adhesive composition, the content of the acrylic copolymer is not particularly limited, but is preferably greater than 50% by mass in the adhesive composition (i.e., is the main component in the adhesive composition). By making the content of the acrylic copolymer greater than 50% by mass, the adhesive composition becomes more transparent, and the optical transparency of the adhesive composition is further improved.

[0091] In the above-mentioned first configuration, the adhesive composition of the present invention contains tackifier resin T1.

[0092] The tackifier resin T1 is at least one tackifier resin selected from the group consisting of terpene phenol resins, hydrogenated terpene phenol resins and xylene resins.

[0093] The polarity of the above-mentioned tackifying resin T1 is higher, and the compatibility with the above-mentioned acrylic copolymer is good, so it is easy to be introduced into the inside of the above-mentioned acrylic copolymer. As a result, it is possible to suppress the formation of approximate crosslinking points caused by the interaction of the structural units of the olefin polymer with polymerizable unsaturated double bonds at the above-mentioned terminal with low polarity from the tackifying resin, so the bonding force of the above-mentioned adhesive composition can be improved under the state of maintaining the excellent bonding force of the above-mentioned acrylic copolymer. In addition, as mentioned above, since the above-mentioned tackifying resin T1 is easily introduced into the inside of the above-mentioned acrylic copolymer, the above-mentioned adhesive composition can suppress turbidity and has excellent optical transparency. In addition, the above-mentioned tackifying resin T1 does not have polymerizable unsaturated double bonds in the molecular structure, and has the property of being not easily oxidized, so the above-mentioned adhesive composition can suppress yellowing, and is not easy to lose optical transparency even if used for a long time.

[0094] It should be noted that the above-mentioned tackifier resin T1 may be used alone or in combination of two or more.

[0095] The tackifier resin T1 preferably includes at least one selected from the terpene phenol resin and the hydrogenated terpene phenol resin. By making the tackifier resin T1 include at least one selected from the terpene phenol resin and the hydrogenated terpene phenol resin, the tackifier resin T1 has a hydroxyl group, and the interaction with the adherend is further improved, thereby further improving the adhesive force of the adhesive composition.

[0096] Among them, the hydrogenated terpene phenol resin is more preferred because the resin has a light color and excellent optical transparency.

[0097] The terpene-phenol resin is a resin obtained by polymerizing a terpene compound in the presence of a phenol compound.

[0098] Examples of the phenol compound include phenol, cresol, xylenol, propylphenol, nonylphenol (Japanese: ノリルフェノール), methoxyphenol, bromophenol, bisphenol A, bisphenol F, bisphenol S, dihydroxynaphthalene, resorcinol, catechol, hydroquinone, pyrogallol, 1,2,4-trihydroxybenzene, and phloroglucinol.

[0099] Examples of the terpene compound include α-pinene, β-pinene, limonene, dipentene, δ-3-carene, dimethyloctatriene, alloocimene, myrcene, ocimene, linalool, and cosmene.

[0100] In addition, other compounds may be further polymerized in the above-mentioned terpene-phenol resin.

[0101] In addition, the above-mentioned phenol compound, the above-mentioned terpene compound, and the above-mentioned other compound may be used alone, or two or more kinds thereof may be used in combination.

[0102] A commercially available product may be used as the terpene-phenol resin. Examples of the commercially available product include YS Polyster G150 (manufactured by Yasuhara Chemical Co., Ltd.).

[0103] The hydrogenated terpene-phenol resin is a resin in which the unsaturated bonds in the terpene-phenol resin are reduced to saturated bonds by hydrogenation. For example, the benzene rings in the terpene-phenol resin are converted to cyclohexane rings by hydrogenation.

[0104] As a method of hydrogenating the terpene-phenol resin, the following method etc. are mentioned, for example.

[0105] That is, the following method can be cited: after dissolving the above-mentioned terpene-phenol resin in purified and dried cyclohexane in a manner such that the polymer concentration becomes 5% by mass, a hydrogenation reaction is started with stirring at a hydrogen supply pressure of 0.7 MPa-Gauge and a reaction temperature of 80°C. When the absorption of hydrogen is completed, the reaction solution is returned to normal temperature and pressure and taken out from the reactor, thereby obtaining the above-mentioned hydrogenated terpene-phenol resin.

[0106] A commercially available product may be used as the hydrogenated terpene-phenol resin. Examples of the commercially available product include YS Polyster UH115 (manufactured by Yasuhara Chemical Co., Ltd.).

[0107] The xylene resin is a resin obtained by reacting and polymerizing m-xylene and formaldehyde in the presence of an acid catalyst.

[0108] In addition, other compounds may be further polymerized in the xylene resin, and preferably phenol compounds are polymerized in the xylene resin. By polymerizing the phenol compounds in the xylene resin, the polarity of the tackifier resin T1 becomes larger and the compatibility with the acrylic copolymer becomes better, so that the adhesive force of the adhesive composition is further improved.

[0109] As the phenol compound to be polymerized in the xylene resin, the same phenol compound as the phenol compound to be polymerized in the terpene phenol resin can be used.

[0110] In addition, the above-mentioned other compounds may be used alone or in combination of two or more.

[0111] A commercially available product may be used as the xylene resin, and examples of the commercially available product include GHP-150 (manufactured by Fudow).

[0112] Relative to 100 parts by mass of the acrylic copolymer, the lower limit of the content of the tackifying resin T1 is 5 parts by mass, and the upper limit is 50 parts by mass. By making the content of the tackifying resin T1 be more than 5 parts by mass, the adhesive composition bonding force is improved. By making the content of the tackifying resin T1 be less than 50 parts by mass, the adhesive composition will not become too hard, and the bonding force of the adhesive composition is improved. The preferred lower limit of the content of the tackifying resin T1 is 10 parts by mass, and the more preferred lower limit is 15 parts by mass, and the preferred upper limit is 45 parts by mass, and the more preferred upper limit is 40 parts by mass.

[0113] In the first configuration, the adhesive composition of the present invention does not contain a tackifying resin T2 different from a terpene-phenol resin, a hydrogenated terpene-phenol resin, and a xylene resin, or contains the tackifying resin T2. ​​When the adhesive composition contains the tackifying resin T2, the upper limit of the content of the tackifying resin T2 is 10 parts by mass relative to 100 parts by mass of the acrylic copolymer. By making the adhesive composition of the present invention not contain the tackifying resin T2 or contain the tackifying resin T2, when the adhesive composition contains the tackifying resin T2, the content of the tackifying resin T2 is less than 10 parts by mass, so that the adhesive composition can suppress turbidity and yellowing, and has excellent optical transparency. When the adhesive composition contains the tackifying resin T2, the preferred upper limit of the content of the tackifying resin T2 is 5 parts by mass.

[0114] In the pressure-sensitive adhesive composition, the content of the tackifier resin T1 is preferably greater than the content of the tackifier resin T2. ​​When the content of the tackifier resin T1 is greater than the content of the tackifier resin T2, the optical transparency of the pressure-sensitive adhesive composition is further improved.

[0115] In the above-mentioned second formation, the adhesive composition of the present invention does not contain tackifying resin or contains tackifying resin, and when containing tackifying resin, relative to 100 parts by mass of the above-mentioned acrylic copolymer, the upper limit of the content of tackifying resin is 5 parts by mass. By making the adhesive composition of the present invention not contain tackifying resin or contain tackifying resin, when containing tackifying resin, the content of tackifying resin is below 5 parts by mass, thus the above-mentioned adhesive composition can further suppress turbidity, yellowing, and optical transparency becomes excellent. When the above-mentioned adhesive composition contains tackifying resin, the preferred upper limit of the content of the above-mentioned tackifying resin is 4 parts by mass.

[0116] In the second configuration, when the adhesive composition contains a tackifier resin, examples of the tackifier resin include terpene phenol resins, hydrogenated terpene phenol resins, xylene resins, etc. Among them, hydrogenated terpene phenol resins are preferred because of their light color and excellent optical transparency.

[0117] The adhesive composition preferably contains a crosslinking agent. By making the adhesive layer contain a crosslinking agent, the acrylic copolymer is crosslinked by the crosslinking agent. By adjusting the degree of crosslinking at this time, the gel fraction of the adhesive layer described later can be adjusted to an appropriate range. It should be noted that in order to make the acrylic copolymer crosslinked by the crosslinking agent, it is preferred that the acrylic copolymer has the structural unit derived from the monomer containing a polar functional group.

[0118] Examples of the crosslinking agent include epoxy crosslinking agents, isocyanate crosslinking agents, etc. Among them, isocyanate crosslinking agents are preferred because the gel fraction of the adhesive layer described later can be easily adjusted to an appropriate range and the adhesive force and holding power of the adhesive tape having the adhesive layer can be further improved.

[0119] The preferred lower limit of the content of the crosslinking agent is 0.05 parts by mass, and the preferred upper limit is 5 parts by mass relative to 100 parts by mass of the acrylic copolymer. By making the content of the crosslinking agent within the above range, it is easy to adjust the gel fraction of the adhesive layer described later to an appropriate range, and the adhesive force and holding power of the adhesive tape having the adhesive layer are further improved. The more preferred lower limit of the content of the crosslinking agent is 0.1 parts by mass, and the more preferred upper limit is 3 parts by mass.

[0120] The adhesive composition may contain conventionally known fine particles and additives such as inorganic fine particles, conductive fine particles, an antioxidant, a foaming agent, an organic filler, and an inorganic filler, as required.

[0121] A pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive composition of the present invention is also one of the present invention.

[0122] The pressure-sensitive adhesive tape of the present invention has a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive composition, and thus can achieve both excellent pressure-sensitive adhesive strength and excellent optical transparency even when the pressure-sensitive adhesive tape is thin.

[0123] The preferred lower limit of the gel fraction of the above-mentioned adhesive layer is 10% by mass, and the preferred upper limit is 80% by mass. By making the gel fraction of the above-mentioned adhesive layer more than 10% by mass, the above-mentioned adhesive layer hardens, and the holding force of the above-mentioned adhesive tape is further improved. In addition, the cohesive force of the body of the above-mentioned adhesive layer becomes larger, and the heat resistance of the above-mentioned adhesive tape is further improved. By making the gel fraction of the above-mentioned adhesive layer less than 80% by mass, the above-mentioned adhesive layer becomes easier to stretch, and the adhesive force of the above-mentioned adhesive tape is further improved. The more preferred lower limit of the gel fraction of the above-mentioned adhesive layer is 15% by mass, and the more preferred upper limit is 75% by mass.

[0124] In addition, the gel fraction of the said pressure-sensitive adhesive layer can be measured by the following method.

[0125] That is, the adhesive layer W0 (g) is collected, immersed in 50 mL of tetrahydrofuran, and shaken for 24 hours using an oscillator at a temperature of 23°C and 200 rpm. After shaking, the adhesive layer that has absorbed tetrahydrofuran and swelled is filtered using a metal mesh (mesh size #200, mass: W1 (g)). After the separated adhesive layer is dried at 110°C for 1 hour, the mass W2 (g) of the adhesive layer including the metal mesh is measured. Then, the obtained W0, W1, and W2 can be measured by a method such as calculating the gel fraction according to the following formula (1).

[0126] Gel fraction (mass %) = 100 × (W2-W1) / W0 (1)

[0127] (W0: mass of initial adhesive layer, W1: initial mass of metal mesh, W2: mass of adhesive layer including metal mesh after drying)

[0128] The preferred upper limit of the thickness of the adhesive layer is 15 μm. By making the thickness of the adhesive layer less than 15 μm, the adhesive tape can be more suitable for fixing small and thin electronic devices, etc. The more preferred upper limit of the thickness of the adhesive layer is 10 μm, and the further preferred upper limit is 5 μm.

[0129] In addition, although the preferred lower limit of the thickness of the pressure-sensitive adhesive layer is not particularly limited, from the viewpoint of the handling properties of the pressure-sensitive adhesive tape, the lower limit is about 2 μm.

[0130] The above-mentioned adhesive tape can be an unsupported type without substrate, or a supported type with the above-mentioned adhesive layer formed on the substrate. Wherein, the above-mentioned adhesive tape preferably does not have an unsupported type of substrate. By making the above-mentioned adhesive tape not have substrate, the thickness of the above-mentioned adhesive tape becomes thinner, and in addition, the optical transparency of the above-mentioned adhesive tape becomes more excellent, so the above-mentioned adhesive tape can be more suitable for the fixing of small, thin electronic equipment, devices, etc.

[0131] When the pressure-sensitive adhesive tape has a substrate, it may be a single-sided pressure-sensitive adhesive tape having the pressure-sensitive adhesive layer on one side of the substrate, or a double-sided pressure-sensitive adhesive tape having the pressure-sensitive adhesive layer on both sides of the substrate.

[0132] Examples of the substrate include sheets made of resins such as acrylic resin, olefin, polycarbonate, vinyl chloride, ABS, polyethylene terephthalate (PET), nylon, urethane, and polyimide; sheets having a mesh structure; and sheets having holes.

[0133] The preferred lower limit of the thickness of the substrate is 5 μm, and the preferred upper limit is 10 μm. When the thickness of the substrate is 5 μm or more, the adhesive tape has a moderate stiffness and excellent handling properties. When the thickness of the substrate is 10 μm or less, the adhesive tape can be more suitable for fixing small and thin electronic devices, devices, etc.

[0134] The upper limit of the haze of the substrate at 23°C is preferably 0.5%. When the haze of the substrate at 23°C is 0.5% or less, the optical transparency of the pressure-sensitive adhesive tape becomes excellent. The upper limit of the haze of the substrate at 23°C is more preferably 0.3%.

[0135] The preferred lower limit of the haze of the substrate at 23° C. is not particularly limited, but is preferably closer to 0% from the viewpoint of the optical transparency of the pressure-sensitive adhesive tape.

[0136] The haze of the substrate can be measured, for example, using a haze meter (such as “NDH4000” manufactured by Nippon Denshoku Industries, Ltd.).

[0137] The pressure-sensitive adhesive tape may further include other layers within a range not impairing the effects of the present invention.

[0138] The method for manufacturing the above-mentioned adhesive tape is not particularly limited, and a conventionally known method can be used. For example, first, the above-mentioned (meth) alkyl acrylate, the above-mentioned olefin polymer having a polymerizable unsaturated double bond at the terminal, and the polar functional group monomer as required are copolymerized by a conventional method to obtain the above-mentioned acrylic copolymer. Next, a solution of an adhesive composition formed by combining the above-mentioned acrylic copolymer obtained, and the above-mentioned tackifying resin T1, the above-mentioned tackifying resin T2 and other additives as required is applied to a film subjected to a demoulding treatment, and dried, thereby enabling the manufacture. In addition, the adhesive tape manufactured by the above-mentioned method can also be made into a support-type adhesive tape by using the adhesive tape manufactured by the above-mentioned method as an adhesive layer and laminating it with a substrate.

[0139] When the thickness of the adhesive layer is 15 μm or less, after the adhesive tape is attached and left to stand at 23°C for 24 hours, the preferred lower limit of the 180° peeling force on the glass at 23°C is 9 N / inch. By making the 180° peeling force on the glass at 23°C to be 9 N / inch or more after the adhesive layer is attached and left to stand at 23°C for 24 hours, the adhesive tape can be more suitably used for fixing small and thin electronic devices, etc. The more preferred lower limit of the 180° peeling force on the glass at 23°C after the adhesive tape is attached and left to stand at 23°C for 24 hours is 10 N / inch.

[0140] Furthermore, the preferred upper limit of the 180° peel strength to glass at 23° C. after the pressure-sensitive adhesive tape is affixed and left to stand at 23° C. for 24 hours is not particularly limited.

[0141] In addition, after the said adhesive tape is affixed and left to stand at 23 degreeC for 24 hours, the 180 degree peeling strength with respect to glass at 23 degreeC can be measured by the following method etc.

[0142] That is, the above-mentioned adhesive tape having the above-mentioned adhesive layer is cut into a plane rectangle of 25 mm in width and 60 mm in length to prepare a test piece, and then the obtained test piece is bonded to a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., "Large SLIDE GLASS White Edged No. 2") using a 2 kg hand roller. Then, after standing at 23°C for 24 hours, the obtained measurement sample is subjected to a 180° peel test at 23°C and a tensile speed of 300 mm / min using a tensile testing machine (manufactured by A&D Co., Ltd., "RTI-1310" etc.) in accordance with JIS Z0237:2009. After bonding, the 180° peel force to the glass at 23°C after standing at 23°C for 24 hours can be measured, and the like.

[0143] The upper limit of the haze of the pressure-sensitive adhesive tape at 23°C is preferably 1.0%. If the haze of the pressure-sensitive adhesive tape at 23°C is 1.0% or less, the optical transparency of the pressure-sensitive adhesive tape becomes more excellent. The upper limit of the haze of the pressure-sensitive adhesive tape at 23°C is more preferably 0.5%, and the upper limit is still more preferably 0.3%.

[0144] The preferred lower limit of the haze of the pressure-sensitive adhesive tape at 23° C. is not particularly limited, but is preferably closer to 0% from the viewpoint of the optical transparency of the pressure-sensitive adhesive tape.

[0145] In addition, the haze of the said pressure-sensitive adhesive tape at 23 degreeC can be measured by the following method etc.

[0146] That is, the above-mentioned adhesive tape (adhesive layer thickness: 5 μm) is cut into a 40 mm×40 mm plane rectangle, and the polyethylene terephthalate film on one side of the cut adhesive tape is peeled off, and the tape is laminated on a soda-lime glass (0.7 mm×56 mm×86.6 mm) using a 2 kg hand roller. Then, the polyethylene terephthalate film on the other side of the laminated adhesive tape is peeled off, and the measurement can be performed at room temperature (23° C.) using a spectrophotometer (manufactured by Konica Minolta, “CM-3700”, etc.) by using the SCI method to evaluate the light transmitted from the single-layer sheet surface to the soda-lime glass surface.

[0147] The yellowness b of the adhesive tape at 23°C * The upper limit of the preferred value is 0.4. * When the yellowness b value is 0.4 or less, the optical transparency of the pressure-sensitive adhesive tape becomes more excellent. * A more preferred upper limit of is 0.2.

[0148] It should be noted that the yellowness b of the above adhesive tape at 23°C is * The measurement can be performed by the following method.

[0149] That is, the above-mentioned adhesive tape (adhesive layer thickness: 15 μm) was cut into a 40 mm×40 mm plane rectangle, and the polyethylene terephthalate film on one side of the cut adhesive tape was peeled off, and the tape was laminated on a soda-lime glass (0.7 mm×56 mm×86.6 mm) using a 2 kg hand roller. Then, the polyethylene terephthalate film on the other side of the laminated adhesive tape was peeled off, and the color was measured at room temperature (23° C.) using a spectrophotometer (manufactured by Konica Minolta, “CM-3700”, etc.) by using the SCI method to evaluate the light transmitted from the single-layer sheet surface to the soda-lime glass surface.

[0150] The yellowness of the adhesive tape after heating at 85°C for 500 hours is * The upper limit of the preferred value is 0.4. The yellowness b of the adhesive tape after heating at 85°C for 500 hours is * When the optical transparency of the adhesive tape is 0.4 or less, the optical transparency of the adhesive tape becomes better. In addition, the adhesive tape is less likely to lose its optical transparency even after long-term use. The yellowness b of the adhesive tape after heating at 85°C for 500 hours is * A more preferred upper limit of is 0.2.

[0151] It should be noted that the yellowness of the adhesive tape after heating at 85°C for 500 hours is * The measurement can be performed by the following method.

[0152] That is, the adhesive tape (adhesive layer thickness: 15 μm) was cut into a 40 mm × 40 mm plane rectangle, and the cut adhesive tape was heated at 85° C. for 500 hours in an oven. Then, the heated adhesive tape was cooled to room temperature (23° C.) by natural cooling, and the polyethylene terephthalate film on one side was peeled off and bonded to soda lime glass (0.7 mm × 56 mm × 86.6 mm) by a hand roller. Then, the polyethylene terephthalate film on the other side of the bonded adhesive tape was peeled off, and the measurement was performed at room temperature (23° C.) using a spectrophotometer (manufactured by Konica Minolta, "CM-3700", etc.) by using the SCI method to evaluate the light transmitted from the single-layer sheet surface to the soda lime glass surface.

[0153] The use of the adhesive tape of the present invention is not particularly limited, and since it has excellent adhesive force and excellent optical transparency, it is suitable for use in bonding optical components such as electronic devices and devices. Among them, the adhesive tape of the present invention can exert excellent adhesive force and excellent optical transparency even when the thickness of the adhesive layer is thin, and thus can be more suitable for fixing small and thin electronic devices, devices, etc.

[0154] Effects of the Invention

[0155] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition that can achieve both excellent adhesive strength and excellent optical transparency even when the coating thickness is small. In addition, according to the present invention, it is possible to provide a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive composition. DETAILED DESCRIPTION

[0156] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0157] (Synthesis of acrylic copolymers A to S)

[0158] After adding 300 mL of ethyl acetate and the structural unit monomers shown in Tables 1 to 2 to a reactor equipped with a thermometer, a stirrer, and a cooling tube, the reactor was heated and reflux was started. Next, 0.01 parts by mass of 1,1-bis(tert-hexylperoxide)-3,3,5-trimethylcyclohexane as a polymerization initiator was added to the above reactor to initiate polymerization under reflux. Then, 0.01 parts by mass of 1,1-bis(tert-hexylperoxide)-3,3,5-trimethylcyclohexane was added 1 hour and 2 hours after the start of polymerization, and further, 0.05 parts by mass of tert-hexyl peroxypivalate was added 4 hours after the start of polymerization to continue the polymerization reaction. Then, the polymerization reaction was carried out for a total of 8 hours from the start of polymerization to obtain an ethyl acetate solution containing acrylic copolymers A to S. It should be noted that L-1253 (manufactured by Kuraray Co., Ltd.) was used for the ethylene-butene macromonomer shown in Tables 1 to 2.

[0159] The obtained acrylic copolymer was subjected to polystyrene-equivalent molecular weight distribution measurement using gel permeation chromatography (GPC) (manufactured by Waters, "2690 Separations Module") under the following conditions. The weight average molecular weight (Mw), number average molecular weight (Mn), and polydispersity coefficient (Mw / Mn) of the acrylic copolymer were determined from the obtained molecular weight distribution curve.

[0160] <GPC measurement conditions>

[0161] Solvent: Tetrahydrofuran

[0162] Sample flow rate: 1mL / min

[0163] Detector: Differential Refractometer RI

[0164] Column: GPC KF-806L (manufactured by Showa Denko K.K.)

[0165] Column temperature (measurement temperature): 40°C

[0166] Injection volume: 20 μL

[0167] [Table 1]

[0168]

[0169]

[0170] (Examples 1-1 to 1-28, 2-1 to 2-19, Comparative Examples 1 to 9)

[0171] (1) Preparation of adhesive composition

[0172] To the obtained ethyl acetate solution containing acrylic copolymers AS, the respective materials were added in the compositions shown in Tables 3 to 8, and the mixture was stirred to obtain a pressure-sensitive adhesive composition.

[0173] (2) Production of adhesive tape

[0174] A polyethylene terephthalate film with one side subjected to a release treatment is prepared. The adhesive composition obtained in the above "(1) Preparation of an adhesive composition" is applied to the release-treated surface of the polyethylene terephthalate film so that the dried film reaches a desired thickness, and dried at 110° C. for 5 minutes to prepare a laminated sheet having an adhesive layer of a desired thickness on the release-treated surface of the polyethylene terephthalate film. Next, a polyethylene terephthalate film with one side subjected to a release treatment is overlapped on the adhesive layer of the obtained laminated sheet to obtain an adhesive tape having an adhesive layer of a desired thickness.

[0175] (3) Gel fraction of adhesive layer

[0176] The adhesive layer W0 (g) was collected from the obtained adhesive tape, and the collected adhesive layer was immersed in 50 mL of tetrahydrofuran and shaken for 24 hours using an oscillator at a temperature of 23°C and 200 rpm. After shaking, the adhesive layer swollen by absorbing tetrahydrofuran was filtered using a metal mesh (mesh #200 mesh, mass: W1 (g)). After the separated adhesive layer was dried at 110°C for 1 hour, the mass W2 (g) of the adhesive layer containing the metal mesh was measured. Then, using the obtained W0, W1 and W2, the gel fraction of the adhesive layer was calculated according to the following formula (1). The results are shown in Tables 3 to 8.

[0177] Gel fraction (mass %) = 100 × (W2-W1) / W0 (1)

[0178] (W0: mass of initial adhesive layer, W1: initial mass of metal mesh, W2: mass of adhesive layer including metal mesh after drying)

[0179] <Evaluation>

[0180] The pressure-sensitive adhesive tapes obtained in Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 3 to 8.

[0181] (Adhesion)

[0182] After preparing an adhesive tape having an adhesive layer thickness of 15 μm by the method of the above-mentioned “(2) Preparation of Adhesive Tape”, the obtained adhesive tape was cut into a flat rectangular shape of 25 mm in width × 60 mm in length to prepare a test piece. Next, the obtained test piece was bonded to a glass plate (“Large SLIDE GLASS White Edged No. 2” manufactured by Matsunami Glass Industries Co., Ltd.) by reciprocating a 2 kg hand roller once at a speed of 300 mm / min. Then, after standing at 23°C for 24 hours, a 180° peel test was performed on the obtained measurement sample using a tensile testing machine (“RTI-1310” manufactured by A&D Co., Ltd.) at 23°C and a tensile speed of 300 mm / min in accordance with JIS Z0237:2009. The 180° peel force of the glass at 23°C after the adhesive tape was attached and the glass was allowed to stand at 23°C for 24 hours was measured.

[0183] The adhesive strength of the adhesive tape was evaluated by evaluating the 180° peeling force on the glass at 23°C after the obtained adhesive was left to stand at 23°C for 24 hours and the case where it was 10 N / inch or more was marked as "◎", the case where it was 9 N / inch or more and less than 10 N / inch was marked as "○", the case where it was 8 N / inch or more and less than 9 N / inch was marked as "△", and the case where it was less than 8 N / inch was marked as "×".

[0184] Also, for an adhesive tape having an adhesive layer thickness of 5 μm, the 180° peel strength to glass at 23° C. after the adhesive tape was attached and allowed to stand at 23° C. for 24 hours was measured in the same manner to evaluate the adhesive strength of the adhesive tape.

[0185] (Optical transparency)

[0186] (1) Haze at 23°C

[0187] After preparing an adhesive tape having an adhesive layer thickness of 5 μm by the method of “(2) Preparation of Adhesive Tape” described above, the obtained adhesive tape was cut into a flat rectangular shape of 40 mm×40 mm. For the cut adhesive tape, the polyethylene terephthalate film on one side was peeled off and the tape was bonded to a soda-lime glass (0.7×56×86.6 mm) by reciprocating once with a 2 kg hand roller at a speed of 300 mm / min. Then, the polyethylene terephthalate film on the other side of the bonded adhesive tape was peeled off, and the haze of the adhesive tape at 23°C was measured at room temperature (23°C) using a spectrophotometer (manufactured by Konica Minolta, “CM-3700”) to evaluate the light transmitted from the single-layer sheet surface to the soda-lime glass surface by using the SCI method.

[0188] The optical transparency of the pressure-sensitive adhesive tape was evaluated by evaluating the haze at 23° C. when it was 0.5% or less, when it was greater than 0.5% and less than 1.0%, when it was greater than 1.0% and less than 1.5%, and when it was greater than 1.5%.

[0189] (2) Yellowness b at 23°C *

[0190] After preparing an adhesive tape having an adhesive layer thickness of 15 μm by the method of “(2) Preparation of Adhesive Tape” described above, the obtained adhesive tape was cut into a flat rectangle of 40 mm × 40 mm. For the cut adhesive tape, the polyethylene terephthalate film on one side was peeled off and the tape was bonded to soda-lime glass (0.7 × 56 × 86.6 mm) by reciprocating once with a 2 kg hand roller at a speed of 300 mm / min. Then, the polyethylene terephthalate film on the other side of the bonded adhesive tape was peeled off and the yellowness b of the adhesive layer at 23°C was evaluated by using a spectrocolorimeter (manufactured by Konica Minolta, “CM-3700”) at room temperature (23°C) using the SCI method. * The measurement was carried out.

[0191] The yellowness b at 23°C * The case of 0.2 or less was marked as "◎", the case of more than 0.2 and 0.4 or less was marked as "○", the case of more than 0.4 and 0.5 or less was marked as "△", and the case of more than 0.5 was marked as "×". The optical transparency of the pressure-sensitive adhesive tape was evaluated.

[0192] (3) Yellowness b after heating at 85°C for 500 hours *

[0193] After preparing an adhesive tape having an adhesive layer thickness of 15 μm by the method of the above-mentioned “(2) Preparation of Adhesive Tape”, the obtained adhesive tape was cut into a flat rectangle of 40 mm×40 mm, and the cut adhesive tape was heated at 85°C for 500 hours in an oven. Then, the heated adhesive tape was cooled to room temperature (23°C) by natural cooling, and the polyethylene terephthalate film on one side was peeled off, and the tape was bonded to soda-lime glass (0.7×56×86.6 mm) by reciprocating once with a 2 kg hand roller at a speed of 300 mm / min. Then, the polyethylene terephthalate film on the other side of the bonded adhesive tape was peeled off, and at room temperature (23°C), a spectrocolorimeter (manufactured by Konica Minolta, “CM-3700”) was used to evaluate the light transmitted from the single-layer sheet surface to the soda-lime glass surface by using the SCI method, and the yellowness b after heating at 85°C for 500 hours was measured. * The measurement was carried out.

[0194] The yellowness b of the obtained product after heating at 85°C for 500 hours * The case of 0.2 or less was marked as "◎", the case of more than 0.2 and 0.4 or less was marked as "○", the case of more than 0.4 and 0.5 or less was marked as "△", and the case of more than 0.5 was marked as "×" to evaluate the optical transparency of the pressure-sensitive adhesive tape.

[0195] (Metal Corrosion)

[0196] The surface of the SUS plate from which the pressure-sensitive adhesive tape was peeled after the 180° peel test of the pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer of 15 μm in the evaluation of the above “(Adhesive Strength)” was visually observed.

[0197] The case where no corrosion was observed on the surface of the SUS plate was marked as “◯”, and the case where corrosion was observed on the surface of the SUS plate was marked as “×”, and the metal corrosiveness of the adhesive composition was evaluated.

[0198] Even when the evaluation is "×", the adhesive composition of the present invention can achieve both excellent adhesive strength and excellent optical transparency even when the thickness is thin, and therefore can be used without problems depending on the application.

[0199] [Table 3]

[0200]

[0201]

[0202]

[0203]

[0204]

[0205]

[0206] Industrial Applicability

[0207] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition that can achieve both excellent adhesive strength and excellent optical transparency even when the coating thickness is small. In addition, according to the present invention, it is possible to provide a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive composition.

Claims

1. An adhesive composition, characterized in that An acrylic copolymer comprising a structural unit derived from an alkyl (meth)acrylate and a structural unit derived from an olefin polymer having a polymerizable unsaturated double bond at a terminal, The adhesive composition satisfies at least one structure selected from the following first structure and the following second structure, The first configuration comprises at least one tackifier resin T1 selected from the group consisting of terpene phenol resins, hydrogenated terpene phenol resins and xylene resins, The content of the tackifier resin T1 is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the acrylic copolymer. The adhesive composition does not contain a tackifier resin T2 different from the terpene phenol resin, the hydrogenated terpene phenol resin and the xylene resin, or contains the tackifier resin T2. ​​When the adhesive composition contains the tackifier resin T2, the content of the tackifier resin T2 is 10 parts by mass or less relative to 100 parts by mass of the acrylic copolymer; The second configuration: the acrylic copolymer has a structural unit derived from a monomer containing a polar functional group, The acrylic copolymer has a structural unit derived from an alkyl (meth)acrylate having an alkyl group with 1 to 4 carbon atoms bonded to an oxygen atom of an ester bond. In the acrylic copolymer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester having 1 to 4 carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 30% by mass to 90% by mass, The pressure-sensitive adhesive composition contains no tackifier resin or contains a tackifier resin. When the tackifier resin is contained, the content of the tackifier resin is 5 parts by mass or less based on 100 parts by mass of the acrylic copolymer.

2. The adhesive composition according to claim 1, wherein In the first configuration, the acrylic copolymer has a structural unit derived from a polar functional group-containing monomer.

3. The adhesive composition according to claim 1 or 2, wherein The structural unit derived from a monomer containing a polar functional group includes at least one structural unit selected from a structural unit derived from a monomer containing a carboxyl group and a structural unit derived from a monomer containing a hydroxyl group.

4. The adhesive composition according to claim 3, wherein The structural unit derived from the monomer containing a polar functional group includes the structural unit derived from the monomer containing a carboxyl group.

5. The adhesive composition according to claim 4, wherein In the second configuration, in the acrylic copolymer, the content of the structural unit derived from the carboxyl group-containing monomer is 10% by mass or less.

6. The adhesive composition according to claim 4 or 5, wherein In the acrylic copolymer, the content of the structural unit derived from the carboxyl group-containing monomer is 1% by mass or less.

7. The adhesive composition according to claim 3, 4, 5 or 6, wherein: The structural unit derived from the polar functional group-containing monomer includes the structural unit derived from the hydroxyl group-containing monomer.

8. The adhesive composition according to claim 1, 2, 3, 4, 5, 6 or 7, wherein In the first configuration, the tackifier resin T1 includes the hydrogenated terpene phenol resin.

9. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7 or 8, wherein In the second configuration, the acrylic copolymer has a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 1 to 2 carbon atoms bonded to an oxygen atom in an ester bond. In the acrylic copolymer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester having 1 to 2 carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 10% by mass to 60% by mass.

10. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein In the second configuration, the acrylic copolymer has a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 3 or more and 4 or less carbon atoms bonded to an oxygen atom in an ester bond. In the acrylic copolymer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester having 3 or more and 4 or less carbon atoms in the alkyl group bonded to the oxygen atom of the ester bond is 60% by mass or more.

11. An adhesive tape comprising an adhesive layer comprising the adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

12. The adhesive tape according to claim 11, wherein The gel fraction of the pressure-sensitive adhesive layer is 10% by mass or more and 80% by mass or less.

13. The adhesive tape according to claim 11 or 12, wherein The adhesive layer has a thickness of 15 μm or less.

14. The adhesive tape according to claim 13, wherein after being left to stand at 23°C for 24 hours after being attached, the adhesive tape has a 180° peeling force on glass at 23°C of 9 N / inch or more. 15 . The pressure-sensitive adhesive tape according to claim 11 , 12 , 13 or 14 , which has a haze of 1.0% or less at 23° C.

16. The adhesive tape according to claim 11, 12, 13, 14 or 15, which has no substrate.

Citation Information

Patent Citations

  • Impact-absorbing tape

    JP2009242541A

  • Pressure-sensitive adhesive sheet for front plate of display device

    JP2009258274A

  • Tacky adhesive and tacky adhesive sheet

    JP2012214544A